Imitation of KPOP IDOL's dress styles in the school wear of selected Filipino college KPOP fans - Brolagda, Ariana Ana dela Cruz (College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT Hallyuwave has influenced the Philippines in food and entertainment (Flores, 2012). But has it influenced Filipino Fashion as well? Fashion as a reflection of society (Craik, 2009) may explain the influence of the Hallyuwave phenomenon in Filipino Fashion, specifically by looking at the school wear of Kpop fans. This study aimed to describe the imitation of Kpop idol's dress styles in the school wear of college Filipino Kpop fans. There were 47 college Kpop fans who participated in the study. They were selected through snow ball sampling. A self-administered questionnaire was used to identify the types of Kpop fans, describe the school wear the Kpop fans imitated from their favorite Kpop idol, imitate their Kpop idols. Through cluster analysis, the respondents were classified into four types of fans: the silent rational fans, the average fans, the silent pathological fans, and the active pathological fans. Regardless of their type, fans mostly imitate a certain aspect of the outfit of their favorite Kpop idol and mix it with their personal style. Moreover, if the fan is not expressive as a Kpop fan, they would rarely imitate their Kpop idol's dress style. The fans may also subconsciously imitate the dress styles of their Kpop idols. The research concludes that Hallyuwave influences Philippine Fashion by providing an inspiration for the dress style as seen in the selected young Kpop fans in the study. The results of the study can be applied to researches on social psychology of dress and fashion marketing on Filipino Kpop Fans. The researcher recommends considering a bigger sample population, focusing on other forms of everyday wear, and continuing the visual analysis for further studies.